Some issues on supporting cooperative work in stand-alone environments - Marcos, Adérito (2012)
In this article are presented some issues on integrating cooperative facilities in stand-alone environments, by a transparent and independent manner, maintaining the local space autonomy. A Framework for a generic support of group work at stand-alone environments is discussed and outlined.